2022
DOI: 10.7759/cureus.23024
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease and Hiatal Hernia After Laparoscopic Sleeve Gastrectomy: A Retrospective Cohort Study

Abstract: Introduction: Laparoscopic sleeve gastrectomy (LSG) has shown good results in terms of weight loss and improvement of obesity-comorbidities, even though its effect on inducing new-onset gastroesophageal reflux disease (GERD) is still a matter of debate. This study aims to estimate the incidence of GERD and hiatal hernia post LSG and to identify associated risk factors of GERD development.Methods: This is a retrospective cohort study of all patients who underwent LSG surgery at the National Guard medical hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
2
3
0
2
Order By: Relevance
“…Our findings indicated a significant correlation between the occurrence of GERD symptoms after LSG and factors such as being female, having preoperative hyperlipidemia, and being of older age. These findings are consistent with those of Almutairi et al [ 28 ], who showed a significant correlation between age, sex, and GERD onset postoperatively. In contrast, Althuwaini et al [ 29 ] reported that a high preoperative BMI might be indicative of a lower occurrence of heartburn after LSG.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings indicated a significant correlation between the occurrence of GERD symptoms after LSG and factors such as being female, having preoperative hyperlipidemia, and being of older age. These findings are consistent with those of Almutairi et al [ 28 ], who showed a significant correlation between age, sex, and GERD onset postoperatively. In contrast, Althuwaini et al [ 29 ] reported that a high preoperative BMI might be indicative of a lower occurrence of heartburn after LSG.…”
Section: Discussionsupporting
confidence: 93%
“…A high risk of hiatal hernia development was also found in patients after SG. Therefore, the study confirms that sleeve resection of the stomach can lead to an increase in the risk of developing GERD and hiatal hernia, which should be considered when choosing this technique for treating obesity [19].…”
Section: клінічна та експериментальна медицина / Clinical and Experim...supporting
confidence: 69%
“…[18] found an association between increasing BMI and the prevalence of GERD, with high BMI being associated with an increased risk of gastroesophageal reflux disease. de Vries et al [19] found that increasing BMI was independently associated with increased inspiratory and expiratory intragastric pressure, which increased the inspiratory gastroesophageal pressure gradient. This study also showed that BMI, intragastric pressure, and gastroesophageal pressure gradient were solid independent predictors of esophageal hiatus hernia, which was the only independent predictor of GERD, and, accordingly, of erosive-ulcerative changes in the gastroesophageal junction.…”
Section: клінічна та експериментальна медицина / Clinical and Experim...mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the risk of developing HH after LSG increased over time. More recently, Almutairi et al published a series of 142 post-LSG patients who were followed up for 24 months [81]. Interestingly, the incidence of GERD was 33.1%, whereas that of de novo HH was only 3.5%.…”
Section: Hiatal Hernia and Sleeve Migration Following Sleeve Gastrectomymentioning
confidence: 99%